2017
DOI: 10.1016/j.bpj.2016.11.436
|View full text |Cite
|
Sign up to set email alerts
|

A Dead-Box Protein Acts through RNA to Promote HIV-1 Rev-RRE Assembly

Abstract: The HIV-1 Rev protein activates nuclear export of unspliced and partially spliced viral RNA transcripts, which encode the viral genome and the genes encoding viral structural proteins, by binding to and oligomerizing on the Rev Response Element (RRE). The human DEAD-box protein 1 (DDX1) enhances the RNA export activity of Rev through an unknown mechanism. Using a single-molecule assembly assay and various DDX1 mutants, we show that DDX1 acts through the RRE RNA to specifically accelerate the nucleation step of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 20 publications
2
5
0
Order By: Relevance
“…In both cases, we observed similar bi-exponential kinetic behavior: rate constants 1.06 ± 0.20 s −1 and 0.16 ± 0.06 s −1 in the presence of DDX21 (Figure 8d left) and 1.38 ± 0.18 s −1 and 0.11 ± 0.02 s −1 in the presence of DDX1 (Figure 8d right). In both cases, the fast phase is predominant, whereas the slow phase corresponds to the Rev binding rate observed in the absence of any DDX protein (0.09 ± 0.01 s −1 ), agreeing with previous results [23]. These results indicate that DDX1 and DDX21 both accelerate binding of the first Rev monomer to the RRE and likely act by a similar mechanism.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…In both cases, we observed similar bi-exponential kinetic behavior: rate constants 1.06 ± 0.20 s −1 and 0.16 ± 0.06 s −1 in the presence of DDX21 (Figure 8d left) and 1.38 ± 0.18 s −1 and 0.11 ± 0.02 s −1 in the presence of DDX1 (Figure 8d right). In both cases, the fast phase is predominant, whereas the slow phase corresponds to the Rev binding rate observed in the absence of any DDX protein (0.09 ± 0.01 s −1 ), agreeing with previous results [23]. These results indicate that DDX1 and DDX21 both accelerate binding of the first Rev monomer to the RRE and likely act by a similar mechanism.…”
Section: Resultssupporting
confidence: 91%
“…As demonstrated previously, the presence of DDX1 increases the proportion of fluorescent signal at higher intensity values, indicating an increase in the number of Rev monomers associated with each RRE molecule (Figure 8c, bottom right panel)[46]. Recently, we showed that DDX1 acts through the RRE RNA to promote Rev-RRE assembly [23, 24]. This ability of DDX1 to promote oligomerization of Rev on the RRE may be a general property shared by other DEAD-box helicases, or this activity might reflect the helicase activities and substrate preferences of a particular helicase.…”
Section: Resultssupporting
confidence: 57%
See 3 more Smart Citations